Organizational Culture and its effect on productivity; the case study of La Community Bank - Dwirantwi, Eric Addo (2013)
A thesis submitted to the Institute Of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of COMMONWEALTH EXECUTIVE MASTERS OF PUBLIC ADMINISTRATION,